Consolidation of Tibia Fractures in Rabbits - Rech Cassanego, Guilherme; Inês Ferreira, Priscila; Marchionatti Pigatto, Anita; Cauduro da Rosa, Carolina; Giovanini da Silva, Janine; Maciel Correa, Marjane; Martins Rodrigues, Raíssa; Dutra Côrrea, Luís Felipe (Acta Scientiae Veterinariae, 2022)
Background: Disorders of the locomotor system are among the main treatments for this species, among the main causes are falls from a cage, arms or stairs and aggression by animals, such as dogs and cats. Biological osteosynthesis promotes early formation of secondary bone callus and allows a less accurate reconstruction of difficult interfragmentary apposition of 100% of the fragments. The objective of this work is to report the method of external immobilization with an aluminum channel aiming at the use of bone biology for the healing of unexposed tibial fractures in 3 rabbits (Oryctolagus cuniculus). Cases: Between 2020 and 2021, 3 cases of rabbits with unexposed tibial fractures were treated at the Veterinary Hospital. The 3 patients were diagnosed through physical examination and radiographic examination. All patients underwent anesthesia, underwent external immobilization with an aluminum channel, received analgesics and anti-inflammatory drugs, and recommended rest and care with the maintenance of external immobilization. Approximately at 30 days of rigid immobilization, all cases were evaluated by means of radiographic examination revealing the formation of bone callus at different post-immobilization times in the case 1 - 30 days, case 2 - 23 days and case 3 - 37 days. Discussion: Some surgical principles in rabbits must be followed, such as preserving vascularity if the open technique is decided, providing adequate diet, controlling edema, promoting analgesia and deciding on closed reduction if the fracture is recent and stable. The external coaptation method is a non-invasive method for the treatment of fractures and is also indicated with a high success rate for fractures of metacarpal, metatarsal and phalange bones in rabbits. The patient's age contributed to the early healing, which corroborates with case 1 (3-month-old), case 2 (6-month-old) and a little later the healing in case 3 (24-month-old), allowing unrestricted use of the member. It is worth reinforcing the point of view which defends that "biological osteosynthesis" promotes a favorable environment, especially in the preservation of the vascular supply of the periosteum when compared to traditional open surgical approaches. In this species, the surgical approach is a challenge due to the fact that the bones break or crack very easily, because the bones have a low density and higher mineral composition. Together, the skeleton represents 7% of the body weight, lower when compared to dogs and cats, which is 12%. In addition to these factors, rabbits are prone to secondary fractures, postoperative infections and rapid development of osteomyelitis, which significantly worsens the prognosis. The aluminum used in the manufacture of the aluminum channel has properties that offer resistance, lightness and radio transparency radiographic examination without removal of the channel, avoiding excessive micro-movement of the focus of the fracture due to lack of stabilization and possible refracture of the tibia. Rigid external immobilization with an aluminum channel was satisfactory in the 3 patients evaluated and preserved bone biology and anatomical axis. The treatment of choice was easy to apply, in addition to enabling better radiographic follow-up, promoting rapid bone healing for patients and early use of limbs without restrictions. However, for the effectiveness of the technique, the collaboration of tutors is essential. Keywords: biological, fracture, immobilization, osteosynthesis, orthopedics. Título: Consolidação de fraturas de tíbia em coelhos Descritores: biológica, fratura, imobilização, osteossíntese, ortopedia.